Analisis Kemampuan Komunikasi Matematis Siswa Berkemampuan Tinggi Ditinjau dari Perbedaan Gender - Eka Nurhidayah; Tio Heriyana (Indo-MathEdu Intellectuals Journal, 2023)
Mathematical communication abilitiess are very important for students to have because through communication, students can explore their mathematical thinking, develop mindsets, and relate one idea to another. Talking about the ability of everyone has different abilities, one of the factors that influence it is gender differences. This study aims to analyze and describe the mathematical communication abilities of high-achieving students in terms of gender differences in class VIII students at MTs Negeri 6 Kuningan. This type of research is descriptive research with a qualitative approach. Subject taking was done by purposive sampling technique. Data collection was obtained through tests, interviews, and documentation. The results showed that students' mathematical communication skills, both male and female students, had nearly as good mathematical communication skills, both in terms of speech and writing. It's just that what distinguishes between male and female students is that male students are more thorough and thorough in the process of doing it in writing compared to female students who experience mistakes.